Security Against Network Attacks in Supervisory Control Systems. Issue 1 (July 2017) - Lima, Públio M.; Alves, Marcos V.S.; Carvalho, Lilian K.; Moreira, Marcos V.
Abstract: Cyber-physical systems (CPSs) integrate computing and communication capabilities to monitor and control physical processes. In order to do so, communication networks are commonly used to connect sensors, actuators, and controllers to monitor and control physical systems. The use of communication networks increases the vulnerability of the CPS to cyber attacks that can drive the system to unsafe states. One of the most powerful cyber attacks is the so-called man-in-the-middle attack, where the intruder can observe, hide, create or replace information in the attacked network channel. We propose in this paper a defense strategy that detects intrusions and prevent damages caused by man-in-the-middle attacks in the sensor and/or control communication channels in supervisory control systems. We also introduce the definition of NA-Safe controllability, and we propose an algorithm to verify this property.